Method for producing particulate oxyhydroxide or oxide
Patent Information
- Application Number
- JP2023560861
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-21
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for producing cathode active materials for lithium-ion batteries, particularly those with high nickel content, fail to achieve optimal energy density and require cumbersome processes.
A method for producing particulate oxyhydroxides or oxides of TM with a bimodal particle size distribution, involving specific pH adjustments, continuous mixing, and heat treatment in the absence of lithium compounds, to create a precursor for electrode active materials.
The method results in a precursor with enhanced energy density and homogeneous physical properties, leading to improved cathode active materials for lithium-ion batteries.
Smart Images

Figure 00000014_0000 
Figure 00000014_0001 
Figure 00000014_0002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a particulate oxyhydroxide or oxide of TM having a bimodal particle size distribution, wherein TM represents a metal and TM comprises nickel and at least one metal selected from cobalt and manganese, said method comprising the following steps: (a) providing an aqueous solution (α1) containing a water-soluble salt of Ni and, optionally, at least one transition metal other than nickel, and an aqueous solution (β1) containing an alkali metal hydroxide, and, optionally, an aqueous solution (γ1) containing a complexing agent selected from ammonia, glycine, tartrate, citrate, and oxalate; (b) combining solution (α1) and solution (β1), and, where applicable, solution (γ1), at a pH value in the range of 10.0 to 14.0, thereby producing particles of hydroxide of TM; (c) removing the particles from step (b) from the liquid by solid-liquid separation; (d) providing an aqueous solution (α2) containing a water-soluble salt of Ni and, optionally, at least one transition metal other than nickel, and an aqueous solution (β2) containing an alkali metal hydroxide, and, optionally, an aqueous solution (γ2) containing a complexing agent selected from ammonia, glycine, tartrate, citrate, and oxalate; (e) combining solution (α2) and solution (β2), and, where applicable, solution (γ2), at a pH value in the range of 10.0 to 14.0, thereby producing particles of hydroxide of TM, with at least one process parameter different from step (b), said process parameter being selected from pH value, residence time, temperature, stirring parameters, complexing agent, and reactor geometry; (f) removing the particles from step (e) from the liquid by solid-liquid separation; (g) combining the particles from step (c) and the particles from step (f) before, after, or during treatment at 80-750° C. in the absence of a lithium compound. Including, wherein steps (b) and (e) are carried out in a continuous mode and at least one of the solutions (α1) and (α2) contains a metal selected from cobalt and manganese. [Background technology]
[0002] Currently, lithiated transition metal oxides are used as electrode active materials in lithium-ion batteries. Extensive research and development has been carried out over the past years to improve properties such as charge density, specific energy, as well as other properties such as cycle life degradation and capacity loss that may adversely affect the life or applicability of lithium-ion batteries. Further efforts have also been made to improve the manufacturing methods.
[0003] In a typical process for the preparation of cathode materials for lithium-ion batteries, a so-called precursor is first formed by co-precipitating a transition metal as a hydroxide, e.g., an oxyhydroxide, which may or may not be basic. The hydroxide is either pre-calcined to convert it to an oxide or oxyhydroxide, or directly mixed with a lithium source, e.g., but not limited to, LiOH, Li2O or Li2CO3, and calcined at high temperature. The lithium source can be used as a hydrate(s) or in a dehydrated form. Calcination or calcination, often also called thermal or heat treatment of the precursor, is usually carried out at temperatures in the range of 600-1000 °C. During the heat treatment, a solid-state reaction takes place to form the electrode active material. The heat treatment is carried out in a heated zone of an oven or kiln.
[0004] A typical class of cathode active materials that provide high energy density contains a large amount of Ni (Ni-rich), e.g., at least 80 mol % Ni relative to the non-lithium metal content. However, the energy density still needs improvement.
[0005] In many cases, the properties of the precursors are reflected to some extent in the properties of the respective electrode active materials, such as particle size distribution, respective transition metal content, etc. Therefore, it is possible to affect the properties of the electrode active materials by manipulating the properties of the precursors. Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, it was an object of the present invention to provide an electrode active material having a high energy density and a simple method for producing the same.
[0007] It has been proposed to make blends, for example bimodal blends, from cathode active materials having different particle sizes, see US 2011 / 0240913, however the proposed method is tedious. [Means for solving the problem]
[0008] Thus, a method as defined at the outset has been found, hereinafter also referred to as the inventive method or the method according to the invention, which is a method for producing a particulate oxyhydroxide or oxide of TM, said particulate oxyhydroxide or oxide then serving as a precursor of the electrode active material and therefore also referred to as precursor. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 shows a schematic of a stirred tank reactor. [Diagram 2] FIG. 2 shows the number-based particle size distribution of IP.1. [Diagram 3] FIG. 3 shows the definition of lateral and vertical (primary) crystallite size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The resulting TM oxyhydroxides or oxides are particulate and have a bimodal number-based particle size distribution. The particle size distribution can be determined by light scattering or laser diffraction or electroacoustic spectroscopy, with laser diffraction being preferred. One maximum of the number-based particle size distribution is preferably in the range of 0.8-2 μm and the other in the range of 2.1-4 μm. In this context, particle size refers to the diameter of the secondary particles.
[0011] In one embodiment of the present invention, the particle shape of the secondary particles of the obtained precursor is spherical, i.e., particles having a spherical shape. Spherical particles include not only particles that are exactly spherical, but also particles in which the difference between the maximum diameter and the minimum diameter of at least 90% (number average) of a representative sample is 10% or less.
[0012] In one embodiment of the invention, the resulting precursor is composed of secondary particles which are agglomerates of primary particles.
[0013] In one embodiment of the invention, the specific surface area (BET) of the resulting precursor is between 2 and 120 m, determined by nitrogen adsorption, for example according to DIN-ISO 9277:2003-05. 2 / g range.
[0014] The precursor is an oxyhydroxide of TM, where TM comprises Ni, at least one transition metal selected from Co and Mn, and optionally at least one further metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta.
[0015] The oxides of TM may contain residual hydroxyl or carbonate groups in the range of 100-1,000 ppm (by mass), as determined, for example, by differential scanning thermogravimetry ("DSC") as mass loss at temperatures ranging from 180 to 450°C.
[0016] In one embodiment of the invention, TM is a compound of the general formula (I) (Nia Co b Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.6 to 0.98, preferably 0.8 to 0.95, and more preferably 0.83 to 0.92, b is in the range of 0.025 to 0.2, preferably 0.025 to 0.15; c is in the range of 0 to 0.3, preferably 0 to 0.15; d is in the range of 0 to 0.1, preferably 0 to 0.05; M is selected from Al, Ti, Zr, Mo, W, Al, Mg, Nb, and Ta; a+b+c=1) It is a combination of metals.
[0017] The TM may contain trace amounts of further metal ions, e.g., trace amounts of ubiquitous metals such as sodium, calcium or zinc, as impurities, but such trace amounts are not considered within the context of this invention, trace amounts in this context meaning amounts of 0.05 mol % or less relative to the total metal content of the TM.
[0018] The method of the present invention comprises the following steps (a) and (b) and (c) and (d) and (e) and (f) and (g), hereinafter also referred to as step (a) and step (b) and step (c) and step (d) and step (e) and step (f) and step (g), or each individually, for brevity (a) or (b) or (c) or (d) or (e) or (f) or (g). The method of the present invention is described in more detail below.
[0019] Step (a) comprises providing an aqueous solution (α1) containing a water-soluble salt of Ni, at least one transition metal selected from Co and Mn, and optionally at least one further metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta, and an aqueous solution (β1) containing an alkali metal hydroxide, and optionally an aqueous solution (γ1) containing a complexing agent selected from ammonia, glycine, tartrate, citrate and oxalate.
[0020] The term water-soluble salts of cobalt and nickel or manganese, or of metals other than nickel and cobalt and manganese, refers to salts that have a solubility in distilled water at 25° C. of 25 g / l or more, the amount of salt being determined under the omission of water of crystallization and water resulting from aquo complexes. The water-soluble salts of nickel and cobalt and manganese are preferably Ni 2+ and Co 2+ and Mn 2+ Examples of water-soluble salts of nickel and cobalt are sulfates, nitrates, acetates and halides, especially chlorides. Preferred are the nitrates and sulfates, of which the sulfates are more preferred.
[0021] Said aqueous solution (α1) preferably contains Ni and the further metal(s) in the relative concentrations intended as the TM of the precursor or in one of the proportions of the precursor.
[0022] Said aqueous solution (α1) preferably contains Ni, and optionally further metal(s), in a total concentration of 0.5 to 2.2 mol / l.
[0023] Solution (α1) may have a pH value in the range of 2 to 5. In embodiments where a higher pH value is desired, ammonia may be added to solution (α1). In another embodiment, no ammonia is added to solution (α1).
[0024] Step (a) further provides an aqueous solution of an alkali metal hydroxide, hereinafter also referred to as solution (β1). Examples of alkali metal hydroxides include lithium hydroxide, preferably potassium hydroxide, and a combination of sodium hydroxide and potassium hydroxide, and even more preferably sodium hydroxide.
[0025] In embodiments in which solution (β1) contains an alkali metal hydroxide, said solution (β1) contains a certain amount, for example 0.1 to 2% by weight based on the amount of the respective alkali metal hydroxide, of carbonate, which is either added intentionally or by aging of the solution or the respective alkali metal hydroxide.
[0026] The solution (β1) may have a concentration of alkali metal hydroxide in the range of 0.1 to 12 mol / l, preferably 6 to 10 mol / l.
[0027] The pH value of the solution (β1) is preferably greater than or equal to 13, for example 14.5. In the context of the present invention, unless stated otherwise, the pH value is determined at 23° C.
[0028] In the method of the invention, ammonia is preferably used. Where applicable, the solution (γ1) contains a complexing agent selected from ammonia, glycine, tartrates, citrates and oxalates. In the context of the present invention, the term glycine includes the compound glycine and its alkali metal salts, such as the potassium salt or preferably the sodium salt. The terms tartrates and oxalates include the respective free acids and the mono- and di-alkali metal salts, such as the mono- or di-potassium salt or the mono- or disodium salt or the mixed salts of sodium and potassium. The term "citrates" includes citric acid and its alkali metal salts, such as the mono- or di- or trisodium salt and the mono-, di- and tripotassium salt.
[0029] In one embodiment of the present invention, the solution (γ1) has an ammonia concentration in the range of 1 to 30 mass %.
[0030] In one embodiment of the present invention, the solution (γ1) contains a complexing agent selected from glycine, tartrate, citrate, and oxalate, or their respective alkali metal salts, in the range of 0.05 to 1.0 mol % relative to TM.
[0031] Step (b) comprises combining solution (α1) and solution (β1), and where applicable solution (γ1), at a pH value in the range of 10.0 to 14.0, preferably 11 to 12.2, thereby producing particles of hydroxide of TM. The particles are slurried in an aqueous medium.
[0032] In one embodiment of the present invention, step (b) is carried out at a temperature in the range of 10 to 85°C, preferably at a temperature in the range of 40 to 65°C.
[0033] In one embodiment of the invention, step (b) is carried out at a pressure in the range of 500 mbar to 10 bar, preferably at ambient pressure.
[0034] Step (b) is carried out in a continuous mode, for example in a plug flow reactor or a cascade of two or more continuous stirred tank reactors, preferably in a single continuous stirred tank reactor, for example a continuous stirred tank reactor with an overflow system.
[0035] In one embodiment of the present invention, step (b) is carried out in a continuous stirred tank reactor operated at an average residence time in the range of from 1 hour to 12 hours, preferably from 3 hours to 7 hours.
[0036] Step (c) involves removing the particles from step (b) from the liquid by a solid-liquid separation technique. Examples of solid-liquid separation techniques include decantation, filtration, or centrifugation, with filtration being preferred, to obtain the particulate material. Following step (c), the particulate material from step (b) may be dried, for example under vacuum or air, at a temperature in the range of 80-140° C. During drying in the presence of air, some oxidation may be observed, particularly in embodiments where the TM contains manganese.
[0037] Step (d) comprises providing an aqueous solution (α2) containing a water-soluble salt of Ni, at least one transition metal selected from Co and Mn, and optionally at least one further metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta, and an aqueous solution (β2) containing an alkali metal hydroxide, and optionally an aqueous solution (γ2) containing ammonia.
[0038] In the context of the present invention, the term "a solution containing a metal" means that such a solution contains a salt of said metal.
[0039] Said aqueous solution (α2) preferably contains Ni and the further metal(s) in the relative concentrations intended as TM of the precursor or in one of the proportions of the precursor.
[0040] The solution (α2) may have the same composition as the solution (α1), or may have a different composition.
[0041] Said aqueous solution (α2) preferably contains Ni, and optionally further metal(s), in a total concentration of 0.1 to 12 mol / l, preferably 6 to 10 mol / l.
[0042] Solution (α2) may have a pH value in the range of 2 to 5. In embodiments where a higher pH value is desired, ammonia may be added to solution (α2).
[0043] In step (a), an aqueous solution of an alkali metal hydroxide is further provided, hereinafter also called solution (β2). Solution (β2) may have a concentration of alkali metal hydroxide ranging from 0.1 to 12 mol / l, preferably from 6 to 10 mol / l.
[0044] The pH value of the solution (β2) is preferably 13 or higher, for example 14.5.
[0045] In the process of the invention it is possible to use ammonia, but it is possible to feed it separately as solution (γ2) or in solution (β2) or in solution (α2).
[0046] The solution (β2) may have the same composition as the solution (β1), or may have a different composition.
[0047] The solution (γ2) may have the same composition as the solution (γ1), or may have a different composition.
[0048] In one embodiment of the present invention, the solution (γ2) has an ammonia concentration in the range of 1 to 30 mass %.
[0049] In one embodiment of the present invention, the solution (γ2) contains a complexing agent selected from glycine, tartrate, citrate, and oxalate, or their respective alkali metal salts, in the range of 0.05 to 1.0 mol % relative to TM.
[0050] Step (e) comprises combining solution (α2) and solution (β2), and, where applicable, solution (γ2), at a pH value in the range of 10.0 to 14.0, preferably 11 to 12.2, thereby producing particles of hydroxide of TM. The particles are slurried in an aqueous medium.
[0051] In one embodiment of the present invention, step (e) is carried out at a temperature in the range of 10 to 85° C., preferably at a temperature in the range of 40 to 65° C. Steps (b) and (e) may be carried out at different temperatures or at the same temperature.
[0052] In one embodiment of the invention, step (e) is carried out at a pressure in the range of 500 mbar to 10 bar, preferably at ambient pressure.
[0053] Step (e) is carried out in a continuous mode, for example in a plug flow reactor or a cascade of two or more continuous stirred tank reactors, preferably step (e) is carried out in a continuous stirred tank reactor, for example a continuous stirred tank reactor with an overflow system.
[0054] In one embodiment of the present invention, step (e) is carried out in a continuous stirred tank reactor operated at an average residence time in the range of from 1 hour to 12 hours, preferably from 3 hours to 7 hours.
[0055] In step (e), at least one process parameter is different from the respective parameter in step (b), said process parameter being selected from pH value, duration, temperature, stirring parameters, complexing agent, residence time, and reactor geometry.
[0056] In one embodiment of the present invention, in steps (b) and (e), the pH values differ by at least 0.1 units, for example 0.2 to 4.0 units, preferably 0.2 to 1.5 units.
[0057] In one embodiment of the invention, the durations determined by the average residence time in steps (b) and (e) differ by at least 1 hour, for example 1 to 5 hours, preferably 1 to 3 hours. A longer residence time leads to larger particulate (oxy)hydroxides, while other parameters remain unchanged.
[0058] In one embodiment of the invention, in steps (b) and (e), the temperature differs by at least 5° C., for example 5-20° C., preferably 5-10° C. Higher temperatures result in larger particulate (oxy)hydroxides, while other parameters remain unchanged.
[0059] In one embodiment of the invention, in steps (b) and (e) the stirring parameters, such as the stirring speed or stirrer geometry, are different or the average energy input is different.
[0060] In one embodiment of the invention, different complexing agents are used in steps (b) and (e), or a complexing agent is used in step (c) but no complexing agent is used in step (e).
[0061] In one embodiment of the invention, different reactor types, sizes, or diameter to height ratios are used in steps (b) and (e), and therefore the reactor geometries are also different.
[0062] Step (f) involves removing the particles from step (e) from the liquid by a solid-liquid separation technique. Examples of solid-liquid separation techniques include decantation, filtration, or centrifugation, with filtration being preferred to obtain such precursor. Following step (f), the particles from step (e) may be dried under air at a temperature in the range of 100-140° C. During the drying process, some oxidation may be observed, especially in embodiments where the TM contains manganese.
[0063] At least one of the solutions (α1) and (α2) contains a metal selected from cobalt and manganese, or both the solutions (α1) and (α2) contain a metal selected from cobalt and manganese.
[0064] In one embodiment of the invention, the compositions of solutions (α1) and (α2) are the same, i.e. they contain the same metals, the deviation from each other being less than 2 mol %. In another embodiment, the compositions of solutions (α1) and (α2) are different from each other.
[0065] In an embodiment in which solutions (α1) and (α2) have different compositions, at least one further process parameter in steps (b) and (e) is different, where different means that the relative concentrations of metals such as nickel differ by at least 3 mol %, preferably 5-10 mol %.
[0066] In a preferred embodiment of the invention, the compositions of solutions (β1) and (β2) are identical.
[0067] Step (g) involves combining the particles from step (c) and the particles from step (f) before, after or during treatment at 80-750°C, preferably 250-700°C, in the absence of lithium compounds.
[0068] Examples of suitable vessels for mixing before or after treatment at 80 to 750°C include all types of mixers, such as air mixers, drum mixers, mixers with horizontal or vertical axis agitators, free-fall mixers, and plowshare mixers.
[0069] The treating in step (g) may be carried out in a rotary kiln, a roller hearth kiln, or a fluidized bed.
[0070] In one embodiment of the invention, said treatment in step (g) has a duration in the range of 30 minutes to 10 hours, preferably 30 minutes to 5 hours, preferably up to 3 hours. In an embodiment in which step (g) is carried out in a rotary kiln, said residence time refers to the average residence time.
[0071] In one embodiment of the invention, the treatment in step (g) is carried out under an atmosphere selected from an inert gas, air, oxygen-enriched or oxygen-depleted air or exhaust gas. Preferred are atmospheres containing oxygen, such as air, oxygen-enriched air or pure oxygen.
[0072] When step (g) is carried out in a rotary kiln, mixing and treatment at 80 to 750° C. may be carried out simultaneously.
[0073] In one embodiment of step (g), during heat treatment, the atmosphere is exchanged, for example, 10 to 1,000 times per hour, to remove humidity and optionally carbon dioxide.
[0074] Although the pressure may be higher or lower than atmospheric pressure, atmospheric pressure is preferred in step (g).
[0075] In the context of step (g), the term "in the absence of lithium compounds" means that the heat treatment is carried out in the presence of less than 3 mol% lithium, preferably less than 1 mol% lithium, even more preferably less than 0.5 mol%, for example 0.001-0.5 mol% of lithium compounds relative to TM. Such lithium compounds may be any lithium compounds typically used to transfer precursors to cathode active materials, such as, but not limited to, lithium hydroxide, lithium carbonate, lithium nitrate or lithium peroxide. If such lithium compounds are present, they usually result from impurities in the vessel in which step (g) is carried out.
[0076] Oxyhydroxides or oxides of TM are obtained that function well as precursors of cathode active materials for lithium ion batteries. If the temperature in step (g) is above 300° C., mainly the oxide is formed. For the purposes of this invention, the term oxyhydroxide is not limited to compounds having a 1:1 molar ratio of oxide anion and hydroxide anion, but to any compound of TM having a molar ratio of oxide to hydroxide ranging from 10:1 to 1:10.
[0077] A further aspect of the invention relates to particulate oxyhydroxides and oxides of TM with a bimodal particle size distribution, hereinafter also referred to as precursors of the invention, in which TM comprises nickel and at least one metal selected from cobalt and manganese, the number distribution of the particle size distribution of said oxyhydroxides or oxides having a first relative maximum of particle size in the range of 0.8-2 μm and a second relative maximum in the range of 2.1-4 μm, the specific surface area (BET) and the primary crystallite size in the vertical direction from X-ray measurements of the particles from the second relative maximum are 1.05-3 times higher compared to the particles from the first relative maximum, the particle size being obtained by dynamic laser scattering or electroacoustic spectroscopy. The second relative maximum refers to the maximum of the particles with the larger average diameter. The first relative maximum refers to the maximum of the particles with the smaller average diameter.
[0078] For purposes of this invention, the term oxyhydroxide is not limited to compounds having a 1:1 molar ratio of oxide anion to hydroxide anion, but rather to any TM compound having a molar ratio of oxide to hydroxide ranging from 10:1 to 1:10.
[0079] Preferably, the particulate oxyhydroxide and oxide have a span ranging from 1 to 3, the span being calculated as [(D90)-(D10)] divided by (D50). The span refers to the span of the whole material. For each volume-based particle size, (D10) refers to the 10% median, (D90) refers to the 90% median, and D50 refers to the 50% median.
[0080] In one embodiment of the invention, the precursor of the invention has a number-based particle size distribution that corresponds to the superposition of the particle size distributions of two materials, one with a relative maximum in particle size in the range of 0.8-2 μm and the other with a relative maximum in the range of 2.1-4 μm, each material having a span in the range of 0.8-1.7.
[0081] In one embodiment of the invention, the precursor of the invention has a particle size distribution that corresponds to a mixture of two materials, where the two materials have essentially the same elemental composition, essentially the same in this context means that the mole percent of the major components differs by less than 1 mole percent relative to the TM.
[0082] In one embodiment of the invention, the precursor of the invention has a number-based particle size distribution corresponding to a mixture of two materials, where the two materials have different elemental compositions, e.g., at least one metal differs by at least 1.5 mol % relative to TM. In a preferred embodiment, the particles of the second maximum have a higher nickel content than the particles of the first maximum, e.g., 5% or more higher.
[0083] In one embodiment of the present invention, the precursor of the present invention is selected from oxyhydroxides and oxides of TM, where TM is represented by the general formula (I) (Ni a Cob Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.6 to 0.98, preferably 0.8 to 0.95, and more preferably 0.83 to 0.92, b is in the range of 0.025 to 0.2, preferably 0.025 to 0.15; c is in the range of 0 to 0.3, preferably 0 to 0.15; d is in the range of 0 to 0.1, preferably 0 to 0.05; a+b+c=1 and b+c>0) It is a combination of metals.
[0084] The TM may contain trace amounts of further metal ions, e.g., trace amounts of ubiquitous metals such as sodium, calcium or zinc, as impurities, but such trace amounts are not considered within the context of this invention, trace amounts in this context meaning amounts of 0.05 mol % or less relative to the total metal content of the TM.
[0085] The particle size distribution can be determined by light scattering or laser diffraction or electroacoustic spectroscopy, with laser diffraction being preferred. One maximum of the particle size distribution is preferably in the range of 0.8 to 2 μm and the other in the range of 2.1 to 4 μm. In this context, particle size refers to the diameter of the secondary particles.
[0086] In one embodiment of the present invention, the precursors of the present invention may contain residual hydroxyl or carbonate groups in the range of 100 to 1,000 ppm (by mass), as determined by Differential Scanning Thermogravimetry ("DSC") as mass loss at temperatures in the range of 180 to 450°C.
[0087] In one embodiment of the present invention, the particle shape of the secondary particles of the precursor of the present invention is spherical, i.e. the particles have a spherical shape. Spherical spheres include not only particles that are exactly spherical, but also particles in which the difference between the maximum and minimum diameters of at least 90% (number average) of a representative sample is 10% or less.
[0088] In one embodiment of the present invention, the precursor of the present invention is composed of secondary particles that are aggregates of primary particles.
[0089] In one embodiment of the present invention, the specific surface area (BET) of the precursor of the present invention is between 2 and 120 m, determined by nitrogen adsorption, for example according to DIN-ISO 9277:2003-05. 2 / g range.
[0090] The precursor of the present invention is obtainable by the method of the present invention.
[0091] A further aspect of the invention relates to the use of the precursor of the invention for the manufacture of an electrode active material for a lithium ion battery, which precursor is then mixed with a lithium source, such as but not limited to LiOH, Li2O or Li2O2 or Li2CO3, and calcined at high temperature, such as 600-1100°C.
[0092] The invention is further illustrated by examples and figures. EXAMPLES
[0093] General: The drawing shows a schematic of the stirred tank reactor (hereafter reactor 1) in which the preparation of the exemplified precursors was carried out. Reactor 1 is a 50 L stirred vessel equipped with baffles and a cross-arm agitator with a diameter of 0.21 m. RPM: revolutions per minute. All pH measurements were carried out outside reactor 1 at 23°C.
[0094] Powder X-ray diffraction (PXRD) data were collected using a laboratory diffractometer (D8 Discover, Bruker AXS GmbH, Karlsruhe). The instrument was set up with a molybdenum X-ray tube. A curved Germanium Johansson-type primary monochromator was used to monochromatize the characteristic K-α radiation. Data were collected in the Bragg-Brentano reflection geometry, in the range 2θ from 5.0 to 50°, applying a step size of 0.019°. A LYNXEYE area detector was used to collect the scattered X-ray signal.
[0095] For the XRD measurements, the precursors were ground using an IKA tube mill and a MT40.100 disposable grinding chamber. The powder was placed in a sample holder and flattened using a glass plate.
[0096] Rietveld refinement analysis of the microstructure of the precursor materials was performed using DIFFRAC.TOPAS V6 software (Bruker AXS GmbH).
[0097] The BET surface area can be determined according to DIN ISO 9277:2010 by nitrogen adsorption after outgassing the sample at 120° C. for 30 minutes and beyond.
[0098] In the context of the present invention, unless stated otherwise, mean diameter values refer to mass (or volume) distribution.
[0099] Brief description of the drawings: Figure 1: A: Mixing vessel B: Stirrer C: Inner tube of coaxial mixer D: Outer tube of coaxial mixer E: Baffle F: Agitator engine The overflow system is not shown.
[0100] Figure 2: Number-based particle size distribution of IP.1 Figure 3: Definition of lateral and vertical (primary) crystallite size. In this application, both terms are used interchangeably.
[0101] In FIG. 1, the coaxial mixer corresponds to that of WO 2020 / 207901. In step (b.1), the distance between the outlets of the two coaxially arranged pipes C and D was in the range of 15 mm. In step (e.1), the distance between the outlets of the two coaxially arranged pipes C and D was in the range of 40 mm.
[0102] Step (a.1): An aqueous solution of the following was provided: The solution (α1.1) is an aqueous solution of NiSO4, CoSO4 and MnSO4 with a molar ratio of 91:4.5:4.5 and a total transition metal concentration of 1.65 mol / kg. Solution (β1.1) is an aqueous solution of 25% by mass of sodium hydroxide, The solution (γ1.1) was a 25% by mass aqueous ammonia solution.
[0103] Reactor 1 was charged with 40 liters of water heated to 55° C. A solution (γ1.1) in the amount of 929 g was added. The pH of the solution in reactor 1 (measured at 23° C.) was then adjusted to 11.82 with solution (β1.1). The agitator element (pitched blade turbine) was set for constant operation at 420 rpm (average input power ∼12.6 W / l).
[0104] Process (b.1): Solutions (α1.1), (β1.1) and (γ1.1) were introduced simultaneously into reactor 1. The aqueous metal solution was introduced through the inner tube C of the coaxial mixer, and the aqueous sodium hydroxide solution and the aqueous ammonia solution were introduced through the outer tube D of the coaxial mixer. The molar ratio of ammonia to the transition metal of solution (α1.1) was adjusted to 0.25. The formation of a precipitate was observed.
[0105] The sum of the flow rates of solutions (α1.1), (β1.1) and (γ1.1) was set to adjust the average residence time to 5 hours. The flow rate of solution (β1.1) was adjusted by a pH adjustment circuit to maintain the pH value in reactor 1 at a constant value of 11.82 ± 0.05. Reactor 1 was operated continuously while keeping the liquid level in the vessel constant. The mixed hydroxides of Ni, Co and Mn were recovered from reactor 1 by free overflow. The obtained slurry contained about 120 g / l of mixed hydroxides of Ni, Co and Mn.
[0106] Step (c.1): The slurry from step (b.1) was filtered. The resulting filter cake was washed with deionized water, then with an aqueous solution of sodium hydroxide (1 kg of 25 wt % aqueous sodium hydroxide per kg of solid hydroxide), filtered, and dried at 120° C. for 12 hours to obtain mixed oxyhydroxide TM-OOH.1-1. The mixed oxyhydroxide TM-OOH.1-1 had an average particle size (D50) of 6.4 μm, a volume distribution span of 1.54, a tap density of 1.93 g / l, and a pH of 16.4 m. 2 / g. Furthermore, the vertical primary crystallite size determined by X-ray measurements was 6.4 nm.
[0107] Step (d.1): The following aqueous solution was provided: The solution (α2.1) is an aqueous solution of NiSO4, CoSO4 and MnSO4 with a molar ratio of 91:4.5:4.5 and a total transition metal concentration of 1.65 mol / kg. Solution (β2.1) is an aqueous solution of 25% by mass of sodium hydroxide, The solution (γ2.1) was a 25% by mass aqueous ammonia solution.
[0108] Reactor 1 was charged with 40 liters of water heated to 55° C. An amount of 1824.5 g of solution (γ2.1) was added. The pH of the solution in reactor 1 (measured at 23° C.) was then adjusted to 11.76±0.05 with solution (β2.1). The agitator element (pitched blade turbine) was set for constant operation at 420 rpm (average input power ∼12.6 W / l).
[0109] Process (e.1): Solutions (α2.1), (β2.1) and (γ2.1) were introduced simultaneously into reactor 1. The aqueous metal solution was introduced through the inner tube C of the coaxial mixer, and the aqueous sodium hydroxide solution and the aqueous ammonia solution were introduced through the outer tube D of the coaxial mixer. The molar ratio of ammonia to the transition metal of solution (α2.1) was adjusted to 0.5. The formation of a precipitate was observed.
[0110] The sum of the flow rates of solutions (α2.1), (β2.1) and (γ2.1) was set to adjust the average residence time to 5 hours. The flow rate of solution (β2.1) was adjusted by a pH adjustment circuit to maintain the pH value in reactor 1 at a constant value of 11.76 ± 0.05. Reactor 1 was operated continuously while keeping the liquid level in the vessel constant. The mixed hydroxides of Ni, Co and Mn were recovered from reactor 1 by free overflow. The obtained slurry contained about 120 g / l of mixed hydroxides of Ni, Co and Mn.
[0111] Step (f.1): The slurry from step (e.1) was filtered. The resulting filter cake was washed with deionized water, then with an aqueous solution of sodium hydroxide (1 kg of 25 wt % aqueous sodium hydroxide per kg of solid hydroxide), filtered and dried at 120° C. for 12 hours to obtain the mixed hydroxide TM-OOH.1-2. The mixed oxyhydroxide TM-OOH.1-2 had an average particle size (D50) of 15.8 μm, a volume distribution span of 1.264, a tap density of 1.84 g / l and a pH of 25.3 m. 2 / g. Furthermore, the vertical primary crystallite size determined by X-ray measurements was 10.7 nm.
[0112] Step (g.1): The mixed oxyhydroxides TM-OOH.1-1 and TM-OOH.1-2, which were dried separately, were mixed in a mass ratio of 1:1. The particle size distribution was measured by laser diffraction. The span based on the volume distribution was 1.99. The number-based particle size distribution was bimodal, showing a first relative maximum at 1.2 μm and a second relative maximum at 2.4 μm (see FIG. 2). The precursor IP.1 of the present invention was obtained. The BET specific surface area and the vertical primary crystallite size of the particles with the second relative maximum were 1.54 and 1.67 times higher than those of the particles with the first relative maximum.
[0113] IP.1 is ideal for the preparation of cathode active materials: after calcination with a lithium source, cathode active materials were obtained with very high electrode density and very homogeneous physical properties, e.g. with respect to crystallite size.
Claims
1. A method for producing a particulate oxyhydroxide or oxide of TM having a bimodal particle size distribution, comprising the steps of: (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.6 to 0.98; b is 0 or in the range of 0.025 to 0.2; c is in the range of 0 to 0.3; d is in the range of 0 to 0.1; M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb, and Ta; a+b+c=1 and b+c>0) It is a combination of metals by The method comprises the steps of: (a) providing an aqueous solution (α1) containing a water-soluble salt of Ni and, optionally, at least one transition metal other than nickel, and an aqueous solution (β1) containing an alkali metal hydroxide, and, optionally, an aqueous solution (γ1) containing a complexing agent selected from ammonia, glycine, tartrate, citrate, and oxalate; (b) combining solution (α1) and solution (β1), and, if applicable, solution (γ1), at a pH value in the range of 10.0 to 14.0, thereby producing particles of hydroxide of TM; (c) removing the particles from step (b) from the liquid by solid-liquid separation; (d) providing an aqueous solution (α2) containing a water-soluble salt of Ni and, optionally, at least one transition metal other than nickel, and an aqueous solution (β2) containing an alkali metal hydroxide, and, optionally, an aqueous solution (γ2) containing a complexing agent selected from ammonia, glycine, tartrate, citrate, and oxalate; (e) combining solution (α2) and solution (β2), and, if applicable, solution (γ2), at a pH value in the range of 10.0 to 14.0, thereby producing hydroxide particles of TM, wherein at least one process parameter differs from step (b), said process parameter being selected from pH value, residence time, temperature, stirring parameters, complexing agent, and reactor geometry; (f) removing the particles from step (e) from the liquid by solid-liquid separation; (g) combining the particles from step (c) and the particles from step (f) before, after, or during treatment at 80-750° C. in the absence of lithium compounds; Including, steps (b) and (e) are carried out in a continuous mode and at least one of the solutions (α1) and (α2) contains a metal selected from cobalt and manganese, The (oxy)hydroxides or oxides obtained have one maximum in the number-based particle size distribution in the range of 0.8-2 μm and another maximum in the range of 2.1-4 μm, the specific surface area (BET), e.g. determined by nitrogen adsorption according to DIN-ISO 9277:2003-05, and the primary crystallite size in the vertical direction from X-ray measurements of the particles from the second relative maximum are 1.05-3 times higher compared to the particles from the first relative maximum, and the particle size is determined by dynamic laser scattering or electroacoustic spectroscopy.
2. 10. The process of claim 1, wherein step (b) or step (e) is carried out in a continuous stirred tank reactor.
3. 3. The method of claim 1 or 2, comprising the additional step (h) of combining the mixture of particles resulting from step (g) with a lithium source followed by heat treatment.
4. 4. The method according to claim 1 , wherein the compositions of solutions (β1) and (β2) are the same.
5. 5. The process according to claim 1, wherein the metal composition of the particles obtained in steps (c) and (f) is the same.
6. 6. The method according to claim 1, wherein the metal composition of the particles obtained in steps (c) and (f) is different.
7. A particulate oxyhydroxide or oxide of TM having a bimodal particle size distribution, wherein TM is of the general formula (I) (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.6 to 0.98; b is 0 or in the range of 0.025 to 0.2; c is in the range of 0 to 0.3; d is in the range of 0 to 0.1; M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb, and Ta; a+b+c=1 and b+c>0) It is a combination of metals by Particulate oxyhydroxide or oxide, wherein the number-based particle size distribution shows a first relative maximum of particle size in the range of 0.8 to 2 μm and a second relative maximum in the range of 2.1 to 4 μm, the specific surface area (BET) determined by nitrogen adsorption according to DIN-ISO 9277:2003-05 and the primary crystallite size in the vertical direction from X-ray measurements of particles from the second relative maximum are 1.05 to 3 times higher compared to particles from the first relative maximum, and the particle size is determined by dynamic laser scattering or electroacoustic spectroscopy.
8. 8. The particulate oxyhydroxide or oxide of claim 7, wherein the span of the entire material is in the range of 1 to 3, said span being calculated based on the particle size on a volume basis as (D90)-(D10) divided by (D50).
9. 9. A particulate oxyhydroxide or oxide according to claim 7 or 8, wherein the number-based particle size distribution corresponds to a superposition of particle size distributions of two materials, one with a relative maximum of particle size in the range 0.8-2 μm and the other with a relative maximum in the range 2.1-4 μm, each material having a span in the range 0.8-1.7, the span being relative to the volume-based particle size.
10. 10. A particulate oxyhydroxide or oxide according to any one of claims 7 to 9, which corresponds to a mixture of two materials having essentially the same elemental composition.
11. 10. A particulate oxyhydroxide or oxide according to any one of claims 7 to 9, which corresponds to a mixture of two materials having different elemental compositions.
12. 12. A particulate oxyhydroxide or oxide according to any one of claims 7 to 11, in which the particles at the second maximum have a higher nickel content than the particles at the first maximum.
13. 13. Use of the particulate oxyhydroxide or oxide according to any one of claims 7 to 12 for the manufacture of an electrode active material for a lithium ion battery.